(untitled) - Mitsch, William J. (Hoboken, New Jersey, 2015)
The single most important book on wetlands, newly expanded and updated</​b> Wetlands</​i> is the definitive guide to this fragile ecosystem, providing the most comprehensive coverage and in-depth information available in print. Recently updated and expanded, this latest edition contains brand new information on Wetland Ecosystem Services and an updated discussion on Wetland, Carbon, and Climate Change and Wetland Creation and Restoration.
Sinh thái đất ngập nước
Keywords: Sinh thái đất ngập nước,Wetland ecology